2021
DOI: 10.1590/1980-5373-mr-2020-0539
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Investigation of the Effects of Carbon Black Nanoparticles on Hydration Mechanisms, Mechanical and Piezoresistive Properties of Cement Mortars

Abstract: Carbon-black nanoparticles (CBN) have been incorporated into cement-based materials for improvement of mechanical or self-sensing properties. There is no previous research focused on the microstructural evaluation of effects of CBN on both parameters. In this work, mortars containing different CBN contents were produced, cured for 28 days, and subjected to electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopy. Tests for determination of compressive strength, modulus of elasticity and piezor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The electrical resistance was obtained from Ohm's law 41 and, through the electrical circuit in Figure 7, it was possible to determine the electrical resistance (R s ) of the composite by Equation 2 (adapted from 53 ). A DAQ system was used to obtain the voltages in the sample (U s ) and in the circuit supply (U in ), with the use of a reference resistor (R ref ) 1000 Ω 34,54,55 . The data from voltages in the sample (Us) corresponds to the wires green and yellow in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
“…The electrical resistance was obtained from Ohm's law 41 and, through the electrical circuit in Figure 7, it was possible to determine the electrical resistance (R s ) of the composite by Equation 2 (adapted from 53 ). A DAQ system was used to obtain the voltages in the sample (U s ) and in the circuit supply (U in ), with the use of a reference resistor (R ref ) 1000 Ω 34,54,55 . The data from voltages in the sample (Us) corresponds to the wires green and yellow in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
“…Dong et al [82][83][84] obtained a good electrical relationship with the applied compressive stress for cementitious systems both with microencapsulation of carbon black enclosing slaked lime for self-healing purposes and with added polypropylene (PP) fibres for structural enhancement. In a continuation to cyclic compressive loading, Lima et al [85] did not obtain any piezoresistive response from mortar samples with CB additions below 3 wt%, while achieving a maximum average gauge factor of 516 for 6 wt% of carbon black. Similarly, Nalon et al [86,87] observed peak strain sensitivity (GF~1000) in 9 wt% CB-based mortars rehydrated after 200 • C exposure.…”
Section: Bulk Applicationsmentioning
confidence: 96%
“…The addition of micromaterials and nanomaterials in fragile matrices can be considered relevant, as it aims to increase particle packing and improve properties [8]- [10]. Cellulose microparticles can increase chemical interactions with matrices based on mineral binders, acting as a rigid particle in suspensions within composites, and altering the rheological behavior of cementitious systems [1], [10], [11].…”
Section: Introductionmentioning
confidence: 99%